Oversight And Law Enforcement Gaps In Halal Certification Of Imported Products In Indonesia - Muhammad Romi; Sri Indriyani Ali; Adamu Abubakar Muhammad (Yurisprudentia: Jurnal Hukum Ekonomi, 2026)
This study aims to analyze the implementation gaps in the halal product certification system concerning the supervision and law enforcement of halal-certified imported products in Indonesia, particularly in strengthening consumer protection within the global halal trade system. The study employs a qualitative method with a normative juridical approach based on library research. Data were obtained from legislation, institutional reports, court decisions, and relevant academic literature, which were analyzed using the perspectives of law enforcement theory, public policy, halal supply chain management, and maqāṣid al-syarī‘ah. The findings reveal that Indonesia has established a relatively comprehensive regulatory framework through Law No. 33 of 2014 on Halal Product Assurance; however, its implementation remains suboptimal due to institutional fragmentation, overlapping authority among agencies, weak post-certification supervision, limited cross-border verification mechanisms, and the lack of an integrated risk-based monitoring system for imported products. Law enforcement is also constrained by inconsistent sanction implementation, weak inter-agency coordination, and limited supervisory capacity, which potentially undermines public trust in halal certification. Furthermore, differences in international halal standards and the complexity of global supply chains create additional challenges in ensuring halal integrity for imported products. The implications of this study emphasize the necessity of strengthening collaborative governance, harmonizing institutional authority, enhancing digital-based risk supervision, and integrating the principles of maqāṣid al-syarī‘ah into halal consumer protection policies to improve legal certainty, regulatory effectiveness, and public trust in the halal certification system in Indonesia.